Petasites for Migraine Prevention: New Data on Mode of Action, Pharmacology and Safety. A Narrative Review - Borlak, Jürgen; Diener, Hans-Christoph; Kleeberg-Hartmann, Johanna; Messlinger, Karl; Silberstein, Stephen (Frontiers in Neurology, 2022)
Petasins are the pharmacologically active ingredients of butterbur and are of therapeutic benefit in the treatment of migraine and tension headaches. Here, we summarize the pharmacology, safety and clinical efficacy of butterbur in the prevention of migraine attacks and present new data on its mode of action. We review published literature and study reports on the safety and clinical efficacy of the butterbur root extract Petadolex® and summarize new findings on petasins in dampening nociception by desensitizing calcium-conducting TRP ion channels of primary sensory neurons. Importantly, butterbur diminishes the production of inflammatory mediators by inhibiting activities of cyclooxygenases, lipoxygenases and phospholipase A2, desensitizes nociception by acting on TRPA1 and TRPPV1 ion channels, and inhibits the release of calcitonin-gene related peptide (CGRP) of meningeal afferents during migraine attacks. Furthermore, we evaluated the safety of a butterbur root extract in repeated dose studies for up-to 6 month. A no-observable-adverse-effect-level at 15-fold of the maximal clinical dose (3 mg/kg/day MCD) was established for rats. At supratherapeutic doses, i.e. 45–90-fold MCD, we observed bile duct hyperplasia and mechanistic studies revealed regulations of solute carriers to likely account for bile duct proliferations. Additionally, liver function tests performed in cultures of primary human hepatocytes did not evidence hepatotoxicity at therapeutic butterbur and migraine co-medications and in clinical trials, no relevant abnormal liver function was reported. Lastly, in randomized, double-blinded and placebo-controlled trials Petadolex® reduced migraine attack frequency significantly at 150mg/day. Together, butterbur is effective in the prevention of migraine attacks by blocking CGRP signalling.